1980
DOI: 10.1288/00005537-198005001-00001
|View full text |Cite
|
Sign up to set email alerts
|

Later stages of development of the periotic duct and its adjacent area in the human fetus

Abstract: The later stages of development (16–40 weeks in utero) of the periotic duct and its adjacent areas in the human fetus indicate that the critical stages of development occur in four specific time related stages over a six‐week period (20–26 weeks). First, the petrous apex ossifies to separate the inferior cochlear vein into the canal of Cotugno and forms the medial wall of the cochlear aqueduct (22 weeks); second, the canalicular otic capsule fuses with the cochlear otic capsule to obliterate Hyrtl fissure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 99 publications
1
11
0
1
Order By: Relevance
“…There was some variability seen, but unfortunately gestational ages were not reported. Our measurements fill in the informational gap between the lengths of the cochlear aqueduct in the fetus as measured by Spector et al [24] and measurements in adults by Rask-Andersen et al…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…There was some variability seen, but unfortunately gestational ages were not reported. Our measurements fill in the informational gap between the lengths of the cochlear aqueduct in the fetus as measured by Spector et al [24] and measurements in adults by Rask-Andersen et al…”
Section: Discussionsupporting
confidence: 59%
“…At first the cochlear aqueduct is straight, but with progressive ossification and expansion of the otic capsule, it elongates and becomes curved. Spector et al [24] found that from 32 weeks of gestational age to 1 day postpartum there was an increase in the diameter of the external und internal aperture of the aqueduct with development of a funnel-shaped appearance. We also observed this change in our material.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations